Age at menarche and its association with blood pressure in adult women of developing countries: a systematic review and meta-analysis - Gaili Wang; Weihao Shao; Xiaorui Chen; Caifang Zheng; Bowen Zhang; Weidong Zhang (Taylor & Francis Group, 2023)
Context Evidence about the effect of age at menarche (AAM) on blood pressure (BP) has largely been drawn from studies in developed countries. Studies in developing countries are expanding recently but have not been summarised. Objective To systematically explore the association between AAM and BP and the potential modifiers in developing countries. Methods We searched PubMed, Embase, and Web of Science for publications until March 2022. A random-effects model was used to calculate the pooled relative risk (RR) with 95% confidence interval (CI). Results Twenty studies were eligible. In studies with participants' mean age at BP assessment <55 years, women in the oldest group as compared with the middle or the youngest group of AAM had a higher risk of hypertension in those studies without adjustment for confounders (RR 1.79, 95% CI 1.41-2.28, I2=97.0%), those with adjustment for confounders excluding adiposity (1.25,1.04-1.51, I2=84.8%), and those with adjustment for confounders including adiposity (1.38,1.03-1.86, I2=91.8%). In studies with participants' mean age at BP assessment ≥55 years, no significant differences were found for studies without adjustment for confounders (RR 1.07, 95% CI 0.78-1.47, I2=90.3%), studies with adjustment for confounders excluding adiposity (0.85, 0.78-0.92, I2=12.3%), or studies with adjustment for confounders including adiposity (0.95, 0.80-1.11, I2=45.5%). A similar association was observed between AAM and baseline systolic BP and diabolic BP. Conclusion Late menarche was associated with a higher risk of BP and this association was modified by age and adiposity in developing countries.